RELEVANSI TAFSIR AL-IKLI FI MA'ANI AL-TANZIL DENGAN ISU-ISU YANG ADA DI INDONESIA - Kumpulan Harahap; Muhammad Syafii Rangkuti; Romi Ananda; Edi Hermanto (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
The Qur'an holds a central role as a guiding principle for Muslims, offering relevant answers to increasingly complex challenges of the times. Faced with declining understanding, Muslims engage in interpretive efforts to make it a relevant guide for all times and places. Islam facilitates ijtihad to address matters not explicitly detailed in the Qur'an, undertaken by the companions of Prophet Muhammad and subsequent generations. The history of Qur'anic interpretation reveals rich dynamics with diverse approaches such as juridical (fiqhi), philosophical (falsafi), mystical (sufi), and scientific (ilmi). Global Islamic developments drive translations of the Qur'an into various languages, including local languages in Indonesia such as Malay, Sundanese, and Javanese using Pegon script. An exemplary interpretation is "al-Iklil fi Ma'ani al-Tanzil" by KH Mishbah bin Zain al-Mushtafa, popular in Central Java and Yogyakarta. This exegesis not only employs Javanese Pegon script but also responds to the social realities and local community conditions at the time of writing, including traditions and Quranic memorization competitions (MTQ). Overall, this interpretation demonstrates a strong local nuance in interpreting the Qur'an, blending the cultural distinctiveness and traditions of Java in conveying Islamic teachings. It enriches understanding within the Indonesian local context and underscores its significant relevance in an increasingly interconnected global context.